(1.11 ÷ 3.7) x (10^5-(-2)=
To solve this, we start by simplifying the expression inside the parentheses.
10^5 - (-2) can be rewritten as 10^5 + 2, which is equal to 100,000 + 2 = 100,002.
Now, we can substitute this value back into the original expression:
(1.11 ÷ 3.7) x 100,002
Next, we perform the division:
1.11 ÷ 3.7 = 0.3 (rounded to one decimal place).
Finally, we multiply this result by 100,002:
0.3 x 100,002 = 30,000.6.
Therefore, (1.11 ÷ 3.7) x (10^5-(-2) = 30,000.6.
(1.11 ÷ 3.7) x (10^5-(-2)=
1 answer